Citizen science and online data: Opportunities and challenges for snake ecology and action against snakebite. (July 2021) - Durso, Andrew M.; Ruiz de Castañeda, Rafael; Montalcini, Camille; Mondardini, M. Rosa; Fernandez-Marques, Jose L.; Grey, François; Müller, Martin M.; Uetz, Peter; Marshall, Benjamin M.; Gray, Russell J.; Smith, Christopher E.; Becker, Donald; et al.
Abstract: The secretive behavior and life history of snakes makes studying their biology, distribution, and the epidemiology of venomous snakebite challenging. One of the most useful, most versatile, and easiest to collect types of biological data are photographs, particularly those that are connected with geographic location and date-time metadata. Photos verify occurrence records, provide data on phenotypes and ecology, and are often used to illustrate new species descriptions, field guides and identification keys, as well as in training humans and computer vision algorithms to identify snakes. We scoured eleven online and two offline sources of snake photos in an attempt to collect as many photos of as many snake species as possible, and attempt to explain some of the inter-species variation in photograph quantity among global regions and taxonomic groups, and with regard to medical importance, human population density, and range size. We collected a total of 725, 565 photos—between 1 and 48, 696 photos of 3098 of the world's 3879 snake species (79.9%), leaving 781 "most wanted" species with no photos (20.1% of all currently-described species as of the December 2020 release of The Reptile Database). We provide a list of most wanted species sortable by family, continent, authority, and medical importance, and encourage snake photographers worldwide to submit photos and associated metadata, particularly of "missing" species, to the most permanent and useful online archives: The Reptile Database, iNaturalist, and HerpMapper. Graphical abstract: Image 1 Highlights: We collected 725, 565 photos of 3098 snake species (79.9%), leaving 781 "most wanted" species with no photos. A total of 107 countries, mostly developed, small, or insular, have all species represented. Medically-important venomous snakes have more photos in online databases than other species. We provide a list of most wanted species sortable by family, continent, authority, and medical importance. We encourage photographers to submit photos and metadata to The Reptile Database, iNaturalist, & HerpMapper.